Racjonalizacja religii a dominacja społeczna (1). Od Platona do Aureliusza Augustyna i augustynizmu - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2011)
Zbigniew Drozdowicz – RATIONALIZATION OF RELIGION AND SOCIAL DOMINATION. FROM PLATO TO AURELIUS AUGUSTIN AND AUGUSTINISM The inspiration for this paper was (as well two more) is the weberian thesis saying, that the type of rationalization of religion proposed by great intellectuals of their times did led to banishing them from social participation. This thesis is, as to my opinion, far to much exaggerated and a simplification of historical relations between rationalization of religion and the social situation of those, who had made it or supported it. In fact in the past it did happen, that the price for rationalization of religion was the social exclusion of scholars. It also did happen, that those excluded in particular socio- -historical conditions become intellectualy dominant in other and the rationalizations proposed by them did gain wide recognition. This was the case with Plato’s rationalization as well its augustinian continuations and modifications.